Hydrocarbon-Impacted Soils Supported Mn for Organic Pollutant Oxidation - Saputra, Edy; Fadli, Ahmad; Prawiranegara, Barata Aditya; Amri, Amun; Heltina, Desi; Bahri, Syaiful; Sandhyavitri, Ari; Restuhadi, Fajar; Abid, Hussein Rasool; Azhar, Muhammad Rizwan; Utama, Panca Setia (Journal of Applied Materials and Technology, 2023)
Hydrocarbon-impeded soil (HIS) is solid waste from spills or leaks during industrial activities that negatively impact the environment. This study aims to utilize HIS as catalyst support on MnO2 to degrade RhB (RhB) solution using Peroxymonosulfate (PMS) and to determine the optimum conditions for the catalyst to degrade RhB. The catalyst was synthesized by reacting HIS, calcined with KMnO4 with various catalyst supports with high and low Total contain Petroleum Hydrocarbon (TPH). The process degradation of Rhodamine Solution was carried out with various catalysts, PMS, and RhB concentrations. The catalyst was characterized using X-ray diffraction (XRD), Nitrogen gas adsorption-desorption (BET), and Scanning Electron Microscope-Energy Disperse Spectroscope (SEM-EDX). In this study,  the best catalyst performance was MnO2@H-TPH, which could activate PMS to degrade RhB with dye removal of 98% in about 180 min, at conditions 10 g/L RhB, 0.1 g/L catalyst, and 3 g/L PMS with the activation energy of 16.3 kJ/mol.